From drought to desalination: The case of Cape Town - Beerthuis, Sharda (Department of Environmental and Geographical Science, 2022)
The recent Cape Town drought and fear of a severe water crisis between 2015- 2018 was followed by a fast-tracked crisis management response. In line with a wider global trend, the City of Cape Town adopted a technology called ‘reverse osmosis desalination' into the water supply mix. This ‘water production' technology is alluring as it promises to be ‘drought- proof', preserving a constant flow of water in times of increased climatic uncertainty. Yet, the implementation of water technologies in Cape Town continues to be a highly debated topic. Cape Town suffers from a longstanding legacy of uneven racialized infrastructure development practices, resulting in unequal water access and consumption. In this context of unequal water security across social groups and increased climatic vulnerability, it is important to carefully consider the implications of new water technologies if the desired outcome is a more sustainable and equitable water future. Drawing on urban political ecology, this dissertation explores the process in which the instalment of three temporary desalination plants and planning for permanent desalination in Cape Town emerged. This, in order to carefully consider its consequences for equitable water security. By utilizing secondary official city documents, reports and news articles from several credible news platforms, supported by a number of personally conducted semistructured interviews and secondary sourced interviews with City employees, this thesis aims to understand how desalination is constituted as a crisis response. This exploration is organized around analyzing the relationships and dynamics between various actors, the events that signified the processual nature of the adoption and the emergent effects for water access across the City. The findings reveal that the promise that desalination holds as a technical solution to climatic uncertainty undermines the / contradictions that evolve alongside the instalments. While desalination was pushed by the municipality as a drought relief technology for all citizens, the results show that the emergence of this technology came with frictions, as it was contested, ecologically disturbed and critically questioned by multiple actors. As my findings demonstrate, desalination triggers the emergence of exclusive decision-making processes and financial constraints, especially for vulnerable citizens. This thesis thus argues that desalination implies to only secure water for some, while intensifying water insecurity for the already vulnerable. While the City strives towards a “shared water future”, the high focus on extending its water supply to meet growing demands lacks consideration of meeting existing demands, excluding the socio- political processes within current water decision making. This rather reinforces racialized- spatial and distributional inequities across a diverse range of social groups within the City.